EKSPANSI PERKEBUNAN DAN PERTUMBUHAN PENDUDUK DI SUMATRA TIMUR, 1863-1942 - Devi Itawan (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2023)
This paper aims to examine the population growth issue in East Sumatra during the colonial period, which is closely related to the interests of the plantation industry. The limited historiography of East Sumatra underlies this paper because it interprets population growth as a matter of capitalist plantation production relations. East Sumatra has experienced significant population growth since plantation companies initiated and encouraged migration to meet the need for cheap labor for accumulation. Applying historical methods and a political economy approach, this paper emphasizes that population growth directly implies capitalist plantation production relations. An important conclusion from this study is that changes in the population structure in East Sumatra during the colonial period were closely related to the interests of labor issues of the plantation industry. The forced labor regime under the poenale sanction scheme prompted Chinese labour migration. Furthermore, the poenale sanctie eradication has shifted the labor regime to the free worker promoting the colonization program of Javanese coolies. This shift eventually greatly influenced the structure and composition of the East Sumatra population. It is important to note that this study includes the migration outside the interests of the plantation industry, which was carried out independently by residents in the vicinity who were interested in East Sumatra’s economic growth.